2016
DOI: 10.20546/ijcrbp.2016.308.020
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-infective and Antioxidant Activity of Plumbago zeylanica Linn.

Abstract: A b s t r a c t A r t i c l e I n f oPlumbago zeylanica (Plumbaginaceae) is a perennial shrub with semi woody stems and numerous branches. It is used in Africa and Asia for the treatments of common ailments such as haemorrhoids, diarrhoea, leprosy, acute inflammation and cuts. This study aims at evaluating the antimicrobial, anthelmintic and antioxidant activities of P. zeylanica methanol and ethyl acetate leaf extracts. The antimicrobial activity was evaluated by determination of the minimum inhibitory concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Similarly, MEXA leaves significantly inhibited DPPH radical with IC 50 value of 128.3 g/mL. A similar finding was reported by Apenteng et al (14) showing that the ethanol extracts of X. aethiopica fruit (IC 50 0.3612 g/mL) had greater DPPH scavenging potential when compared to the leaves (138.1 g/mL).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similarly, MEXA leaves significantly inhibited DPPH radical with IC 50 value of 128.3 g/mL. A similar finding was reported by Apenteng et al (14) showing that the ethanol extracts of X. aethiopica fruit (IC 50 0.3612 g/mL) had greater DPPH scavenging potential when compared to the leaves (138.1 g/mL).…”
Section: Discussionsupporting
confidence: 84%
“…Although, several studies carried out on X. aethiopica have focussed on the fruit, very little is known about the antioxidant potential of the methanol extract of the leaves. However, very recently, Apenteng et al (14) reported the DPPH scavenging potentials of the ethanol extracts of the fruit and leaves of X. aethiopica. Furthermore, this study assessed the phytochemical content and the antioxidant potentials of the methanol extract of X. aethiopica leaves, with the view to provide a scientific basis for its therapeutic purpose in the treatment and management of cough, malaria, fibroid, amenorrhoea and sickle cell anaemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethyl acetate extracts showed significant (p < 0.0001) concentration-dependent anthelminthic activity with the highest effect at 300 mg/mL causing paralysis at 7.39 ± 0.94 min and death at 11.81 ± 1.10 min. The methanol extract at 300 mg/mL demonstrated slightly lower anthelmintic effect with paralysis at 17.23 ± 1.68 min and death at 21.83 ± 2.60 min [62].…”
Section: Plumbago Zeylanica Linn (Plumbaginaceae)mentioning
confidence: 92%